Rancang Bangun Alat Deteksi Kebocoran Gas LPG Berbasis ESP8266 dengan Notifikasi Telegram - Enno Padlin; Irine Kartika Febrianti; Perawati Perawati; Yudi Irwansi (Uranus: Jurnal Ilmiah Teknik Elektro, Sains dan Informatika, 2025)
Liquefied Petroleum Gas (LPG) leakage remains one of the leading causes of fires in both household and industrial environments, highlighting the urgent need for early detection systems that provide fast and accurate warnings. This study aims to design and implement an LPG leakage detection device based on the ESP8266 microcontroller, utilizing the MQ-6 gas sensor and a real-time notification system through Telegram Bot integration. The system operates by reading LPG gas concentration via the MQ-6 sensor, which is then processed by the ESP8266 to automatically activate a buzzer alarm and a DC fan when gas levels exceed the threshold of 200 ppm. Additionally, the system sends instant alert notifications to the user through the Telegram application, allowing remote monitoring of gas conditions. Real-time gas concentration data are also displayed using a 16x2 LCD for direct visualization. System testing was carried out through controlled gas leakage simulations, and the results showed that the device is capable of responding rapidly, with a reaction time of less than 2 seconds after detection, while consistently providing accurate warnings. The integration of Internet of Things (IoT) technology significantly enhances the effectiveness and efficiency of the system, enabling practical and accessible monitoring. Overall, the developed device demonstrates strong potential as an innovative solution to improve safety, minimize fire risks, and raise public awareness regarding the hazards of LPG leakage, making it suitable for practical application in households and small industries.